Toxicological Assessment of Pure Lolitrem B and Ryegrass Seed Infected with the AR37 Endophyte Using Mice - Finch SC; Hawkes AD; Fitzgerald JM; Broadhurst RB; Staincliffe MR; Munday JS (MDPI (Basel, Switzerland), 2022)
Fungal endophytes in perennial ryegrass are essential to New Zealand's pastoral system due to anti-insect effects. However, endophytes also produce compounds which can be detrimental to animals. Furthermore, as these toxins have been detected in the milk and fat of animals grazing common-toxic (containing lolitrem B) or AR37 endophyte-infected herbage they could enter the human food chain. To assess the risk to human health mice were fed for 90 days with three dose rates of lolitrem B and of AR37. Parameters indicative of animal health were measured as well as chemical, hematological and histological analysis of samples collected on day 90. Since endophyte toxin residues have been detected in milk, they could be transferred from mother to offspring via breast milk. To evaluate possible effects on reproduction two complete generations of mice were fed lolitrem B or AR37. At the dose rates given no adverse effects were observed in either study. The 100-fold safety factor to allow the use of animal data in human health assessments was applied and by considering the concentrations of lolitrem B or AR37 metabolites which could be ingested by a consumer it is highly unlikely that they pose any risk to human health.
Keywords: epoxyjanthitrems; feeding study; lolitrem B; reproduction study; toxicology